2008 IEEE 10th Workshop on Multimedia Signal Processing 2008
DOI: 10.1109/mmsp.2008.4665168
|View full text |Cite
|
Sign up to set email alerts
|

A robust content-based watermarking technique

Abstract: Geometric transformations change the image pixel positions where the watermark is embedded. As a result, a copyright verifier fails to detect the watermark even though the watermark is present in the transformed image. The contentbased watermarking schemes try to solve this problem by first dividing the image into many disjoint patches and then locating those patches with respect to the salient points of the image. Most of the existing content-based schemes are vulnerable to scaling and general affine transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We believe such a fast and robust corner detector can be exploited in various applications including copyright protection [2], image matching [24], photogrammetry [4] and transformed image identification [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe such a fast and robust corner detector can be exploited in various applications including copyright protection [2], image matching [24], photogrammetry [4] and transformed image identification [25].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the distance from a point on the original curve to its location in the smoothed curve is high on and near a corner location but small if it does not have a corner nearby. Consequently, the maxima of the distance function 2 The big-oh notation 'O' denotes the asymptotic upper bound (the worst case running cost) of a function. See [19] for a rigorous definition.…”
Section: Proposed Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the applications (for example, for identification of appropriate image patches in feature-point based image copyright protection schemes [14]) require high repeatability and low localization error of the detected corners. There are also other applications (for example, extraction of building roof lines [1]) that require high repeatability, but may allow some localization error.…”
Section: Performance Studymentioning
confidence: 99%
“…They observed that the hidden information, the information hidden in the cover images, of stego-images are clustered in a plane while all other information of cover images are scattered more evenly in the whole space and have no other clusters. Awrangjeb and Lu [1] proposed micro and macro calibration methods that detect hidden information by calibrating the local and global distribution of the DCT coefficients of the image. All these methods employ high-dimensional feature vectors to describe the difference between cover and covert images, thus significantly affecting their performance in engineering applications.…”
Section: Introductionmentioning
confidence: 99%